Multiply the polynomials using the FOIL method. Express your answer

Kaspaueru2 2021-12-16 Answered
Multiply the polynomials using the FOIL method. Express your answer as a single polynomial in standard form.
(2x+3y)(x-y)
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

accimaroyalde
Answered 2021-12-17 Author has 29 answers
Step 1
FOIL method:
(a+b)(c+d)=ac+ad+bc+bd
Step 2
(2x+3y)(x-y)
multiplication using FOIL method:
= (2x)(x) + (2x)(-y) + (3y)(x) + (3y)(-y)
=2x22xy+3xy3y2
=2x2+xy3y2
=2x2+x1y3y2x0   (x0=1)
polynomial in standard form:
(2x+3y)(xy)=2x2+xy3y2
Not exactly what you’re looking for?
Ask My Question
lalilulelo2k3eq
Answered 2021-12-18 Author has 38 answers
Multiply the terms of the polynomials in the order First, Outer, Inner and Last.
(2x+3y)(xy)=2xx+2x(y)+3yx+3y(y)
Use the laws of exponents to multiply the monomials.
2xx+2x(y)+3yx+3y(y)=2x1+12xy+3xy3y1+1
=2x22xy+3xy3y2
Now, combine the like terms using the distributive property.
2x22xy+3xy3y2=2x2+(2+3)xy3y2
=2x2+xy3y2
Therefore, the product is 2x2+xy3y2.
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more